2016
DOI: 10.1371/journal.pone.0158866
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Sequence of the Oral Pathobiont Strain NI1060 Reveals Unique Strategies for Bacterial Competition and Pathogenicity

Abstract: Strain NI1060 is an oral bacterium responsible for periodontitis in a murine ligature-induced disease model. To better understand its pathogenicity, we have determined the complete sequence of its 2,553,982 bp genome. Although closely related to Pasteurella pneumotropica, a pneumonia-associated rodent commensal based on its 16S rRNA, the NI1060 genomic content suggests that they are different species thriving on different energy sources via alternative metabolic pathways. Genomic and phylogenetic analyses show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…18,23,29,30 Analysis of our data showed that ligation-induced bone loss was observed in all types of mice tested, including WT, TLR2 KO, TLR4 KO, and TLR2&4 KO mice (Figure 2A-D). Analysis further suggested that ligation-induced periodontal bone loss is neither TLR2- nor TLR4-dependent.…”
Section: Discussionmentioning
confidence: 87%
“…18,23,29,30 Analysis of our data showed that ligation-induced bone loss was observed in all types of mice tested, including WT, TLR2 KO, TLR4 KO, and TLR2&4 KO mice (Figure 2A-D). Analysis further suggested that ligation-induced periodontal bone loss is neither TLR2- nor TLR4-dependent.…”
Section: Discussionmentioning
confidence: 87%
“…Clearly, TLR2 and TLR4 KO mice display significantly different oral microbial compositions, therefore differences in the initial microbial composition in the different TLR KO mice preclude definitive conclusions concerning the specific contribution of either TLR2 or TLR4 to P. gingivalis induced disease as has been previously reported . Furthermore, although the presence of N1060, a bacterium shown to initiate periodontitis in mice without the cooperation of the oral microbiota represents a valid study with appropriate conclusions, the observation that it was not found in all the groups of mice underscores the need for a complete oral microbial analysis of the strains being used in all periodontitis mouse model of disease.…”
Section: Discussionmentioning
confidence: 93%
“…Amongst the reference sequences, the 16S rRNA gene sequence of a potentially novel Pasteurellaceae strain, NI1060, was also included into the analysis in an effort to identify and characterize these Pasteurellaceae. NI1060 is a recently identified murine oral bacterium shown to induce periodontitis independently without the cooperation of the oral microbiota in a murine ligature‐induced disease model and found to be closely related to Aggregatibacter actinomycetemcomitans , a species with strong correlation to the development of aggressive periodontitis in humans . Lastly, additional Pasteurellaceae OTUs identified in the samples were also included into this analysis to observe for distinctions between the Pasteurellaceae in TLR KO and WT groups.…”
Section: Resultsmentioning
confidence: 99%
“…Of special note is the presence of a novel murine strain, NI1060, which was found only in mice deficient in both toll‐like receptor‐2 and 4 or wild‐type mice, but not in mice deficient in toll‐like receptor‐2 or toll‐like receptor‐4 alone 67 . The significance of NI1060 is with its high sequence homology to Aggregatibacter actinomycetemcomitans and in its unique ability to induce periodontitis independently without bacterial community cooperation 72,73 . As shown throughout these sections, oral bacteria have the ability to modulate and refine key host defense mediators.…”
Section: Toll‐like Receptor‐2 and 4 Are Involved In The Maintenance Of Homeostasis But Are Not Required For Neutrophil Transitmentioning
confidence: 99%
“…67 The significance of NI1060 is with its high sequence homology to Aggregatibacter actinomycetemcomitans and in its unique ability to induce periodontitis independently without bacterial community cooperation. 72,73 As shown throughout these sections, oral bacteria have the ability to modulate and refine key host defense mediators. Therefore, this suggests that distinct combinations of bacteria within the oral bacterial community have the ability to mount a diverse array of immune responses, which in conjunction with host genetics can further refine and tailor a unique and highly individualized immune response in both health and disease.…”
Section: Cxcl1mentioning
confidence: 99%